Campylobacter jejuni seroepidemiology in native chicken - Rosyidi, Anwar; Budiharta, S; Asmara, W; Yudhabuntara, D (Indonesian Animal Sciences Society, 2012)
Campylobacter jejuni is responsible for about 90% of cases of Campylobacteriosis in humans with gastroenteritis. Healthy chickens can carry Campylobacter spp. in the intestinal tract. Efforts to reduce exposure to Campylobacteriosis by humans may be enhanced by knowledge of its prevalence in poultry. This study aimed to identify factors associated with seropositive response to C. jejuni in native chickens in Mataram. Detection of C. jejuni was accomplished using an immunochromatographic serological method. Association between Campylobacter jejuni seropositive response as the dependent variable with various independent variables was analyzed using ÏÂ² (Chi square) and Odds Ratio (OR). A total of 216 chicken samples were examined and 44 chicken owners were interviewed and their farms examined. Results showed the prevalence of serological response to C. jejuni in chicken samples to be as high as 35.6% and that as many as 70.5% of farms had affected chickens.Â Age of the chicken was the variable most closely associated with incidence of seropositive response, birds older than 3 months more likely to be affected. Variables at the farm level associated with variation in seropositive response were cage type, cage floor material, and origin of drinking water, surface water sources being less desirable. Key Words: Campylobacter jejuni, Seroepidemiology, Native Chicken, Mataram